Eksploitasi Alam dan Ekosistem dalam Novel Bekisar Merah Karya Ahmad Tohari - Nensilianti, Nensilianti; Ridwan; Imelia Kristi Rante Allo (University of Brawijaya, 2025)
This research aims to describe the natural environment written by the results of thoughts or events experienced by a person so that he writes and creates a work, therefore creating a novel. In this study, the novel under study discusses the destruction of nature, exploitation of nature and ecosystems in the novel Bekisar Merah by Ahmad Tohari. The data source of this research is sourced from the internet. Data collection in this study used reading and note-taking techniques. The analysis of Bekisar Merah by Ahmad Tohari uses ecocritical studies. The novel Bekisar Merah can be analyzed using ecocritical theory which involves the study of the relationship between literature and the environment. In this novel, the author subtly describes the people of Karangsoga who work every day as coconut sap collectors to be processed into brown sugar by the lower classes who live in poverty.